Pencegahan dan Penanggulangan Korupsi Oleh Aparat Kepolisian Daerah Lampung - Cici Juliawati (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
Corruption action by police officers is part of law enforcement efforts aimed at preventing and eradicating corrupt practices that are detrimental to the state and society. Corruption, as a criminal act involving abuse of power for personal gain, requires a systematic approach and high integrity from law enforcement, including the police. This article discusses the role of the police in handling corruption cases, the challenges faced in the enforcement process, and the steps needed to increase the effectiveness of law enforcement against criminal acts of corruption. Through policy analysis and case studies, factors that influence the success of enforcement are identified, such as internal corruption, lack of transparency, and coordination between other law enforcement agencies. The conclusions of this research highlight the importance of reform in police institutions, special anti-corruption training, and increased external supervision to create a police force that is clean and has integrity in efforts to eradicate corruption.